Eductainment: A Gamified Learning Management System for Senior High School Subjects with Randomized Algorithm - Polestico, Dariel T.; Torotoro, Piolo N.; Taytayon, Marcela Jane A.; Astoveza, Zerah-Jane M. (2022 2nd International Conference in Information and Computing Research (iCORE), 2022)
The study main objectives were to create a gamified mobile learning management system for senior high school subjects with a randomized algorithm entitled: EducTainment: A Gamified Learning Management System for Senior High School Subjects with Randomized Algorithm. Specifically, the goal of the research was: 1) to create a gamified mobile application with motivational elements. 2) to develop an online learning management system (LMS) with collaborative features for senior high school subjects. 3) to implement a randomized algorithm in teacher quizzes and shops. 4) to evaluate the developed application using the standard (ISO 25010), in relations to; 4.1) functionality, 4.2) portability, 4.3) usability, 4.4) reliability, 4.5) security, 4.6) performance efficiency, 4.7) compatibility, and 4.8) maintainability. The researchers applied the descriptive and developmental methods as the study's research design. The methods were also used to evaluate the strengths and weaknesses of the application. Moreover, the researchers also used the Agile Software methodology as a method used in the development of the application. The researchers have fully developed the gamified application as the nature of the application running environment. The researchers successfully implemented motivational elements such as Pointing Scores, Quizzes, Ranking, Awards/Rewards, Group Activity, and Group Chat. The researchers also successfully implemented its collaborative feature which were Group Activity and Group Chat, and the randomized algorithm was successfully implemented in teacher quizzes. Furthermore, the researchers also have recommendation for future researchers and future use of the application. Future researchers should expand and complex its uniqueness, expand the target user so that everyone can install the application on their mobile phone, and add more relevant features for future use.